Independent review of the Homeland Security Grant Program Terrorism Risk formula and data - Mitch, Ian (HSOAC, 2023)
The Federal Emergency Management Agency's (FEMA's) Homeland Security Grant Program (HSGP) provides a suite of grants to help strengthen U.S. communities against terrorist attacks. To inform grant resource allocation decisions, FEMA has developed and maintains a risk-based formula to assess relative threat, vulnerability, and consequences of terrorist attacks in states and major urban areas. The formula helps FEMA decide how to use finite resources for the grant programs. As a result of the evolving threat landscape and as part of ongoing efforts to improve administration of the grant program, FEMA is performing a comprehensive review of the risk formula. As part of this review, the U.S. Department of Homeland Security (DHS) asked the Homeland Security Operational Analysis Center (HSOAC) to conduct an independent review of HSGP's risk formula and data sources. To assess the grant program's risk formula, the research team evaluated the data elements and sources in each component of the terrorism risk formula, reviewed the mathematical calculations used in the risk methodology, and considered alternative data elements and sources to account for the evolving threat environment. The evaluation framework used in this study addresses the formula's compliance with the program's authorizing language, legitimacy to stakeholders, and the validity and simplicity of the risk formula. The review suggests alternative approaches FEMA could consider to improve the risk formula and to address additional dimensions, such as community resilience and equity